2017
DOI: 10.1007/s00429-017-1532-x
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine increases dopaminergic connectivity in the nucleus accumbens

Abstract: The development of addictive behavior is associated with functional and structural plasticity in the mesocorticolimbic pathway. Increased connectivity upon cocaine administration has been inferred from increases in dendritic spine density, but without observations of presynaptic elements. Recently, we established a method that enables analyses of both dendritic spines and glutamatergic boutons and presented evidence that cocaine induces changes in striatal connectivity. As the pharmacological and behavioral ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Since MSNs arborization is positively regulated by dopamine (Meredith et al, 1995), the higher neuronal arborization observed in GPRIN3 KO mice suggests more dopamine inputs compared with control mice. These suggest a morphological state resembling chronic exposure to cocaine (MacAskill et al, 2014;Spencer et al, 2017;Dos Santos et al, 2018), corroborating our hypothesis that the lack of GPRIN3 induces a "presensitization process. "…”
Section: Discussionsupporting
confidence: 87%
“…Since MSNs arborization is positively regulated by dopamine (Meredith et al, 1995), the higher neuronal arborization observed in GPRIN3 KO mice suggests more dopamine inputs compared with control mice. These suggest a morphological state resembling chronic exposure to cocaine (MacAskill et al, 2014;Spencer et al, 2017;Dos Santos et al, 2018), corroborating our hypothesis that the lack of GPRIN3 induces a "presensitization process. "…”
Section: Discussionsupporting
confidence: 87%
“…We then investigated the postsynaptic subcellular localization of 5-HT4R in dSPNs. The viral construct AAVrh9-PPTA-Cre (AAV-PPTA-Cre), which contains an expression cassette consisting of Cre recombinase driven by the dSPN-specific promoter of the PPTA gene (substance P), and the AAVrh9-pCAG-flex-tdTomato-WRPE (AAV-FLEX-tdTOMATO) construct expressing ''flexed'' tdTomato (Dos Santos et al, 2017;Hikida et al, 2010;Yagishita et al, 2014) were co-injected into the DLS. In dSPNs, we measured the number of co-localizing 5-HT4Rs in 3D-reconstructed dendrites and segmented headspines.…”
Section: -Ht4r Preferentially Localizes At Thalamostriatal Synapsesmentioning
confidence: 99%
“…The DLS was targeted (+0.5 AP; ± 2.6 LM; À2.9 DV) and a volume of 2 ml/site of the mix was injected at a rate of 0.1 ml/min. Mice were perfused 2-3 weeks after the injection (Dos Santos et al, 2017;Hikida et al, 2010). In VGLUT2-Cre mice, double injections of the AAVrh9-PPTA-CRE/AAV9.CAG.Flex.tdTomato.WPRE.bGH mix in the DLS and of AAV9.CAG.Flex.eGFP.WPRE.bGH in the thalamus were also performed.…”
Section: Postsynaptic Localization Of 5-ht4r In Dspnsmentioning
confidence: 99%
“…Some of the earliest work studying the effects of cocaine on midbrain synapses showed that a single in vivo exposure of cocaine was sufficient to alter AMPA channels at excitatory synapses in the VTA . Furthermore, cocaine increases dopaminergic terminal density and striatal spinogenesis, and cocaine withdrawal increases surface‐level AMPARs in the ventral striatum . Related changes in dopamine transmission have also been reported following obesity and HFD exposure.…”
Section: Dopamergic Changes In Substance Use Disordersmentioning
confidence: 99%